Evaluation of the integrated Traditional Chinese and Western medicine nursing for high-risk patients with diabetic foot (高危糖尿病足患者的中西医结合护理干预效果观察) - ZHI Hui (智慧); LIU Jinjing (刘津京); GUO Jing (郭晶); WANG Xiaodi (王晓娣); TONG Fenfei (仝粉飞); ZHENG Wen (郑雯); E Haiyan (鄂海燕); TANG Ling (唐玲) (中西医结合护理)
Objective To investigate the effects of integrated Traditional Chinese and Western medicine nursing on treatment outcome, quality of life and prognosis of high-risk patients with diabetic foot, and provide evidence for more reasonable nursing intervention program. Methods From January 2021to January 2022, 200 patients with type 2 diabetes mellitus were screened; 40 high-risk patients with diabetic foot were eligible and randomly divided in to observation group and control group, with 20 cases in each group. The control group received routine care during the treatment, and those in the observation group received integrated traditional Chinese and Western medicine intervention based on routine care. The treatment outcome, patient quality of life and prognosis of disease were compared between two groups. Results The overall effective rate in the observation group was higher than that in the control group (P＜0. 05). According to the outcome of General Quality of Life Inventory-74(GQOL-74) assessment, the improvement rate in the observation group was 85. 00%(17/20), showing no significant difference compared with 65. 00%(13/20) in the control group (P＞0. 05). The incidences of foot infections and foot ulcers in the observation group were lower than those in the control group (P＜0. 05). Three cases of amputation were reported in the control group. Conclusion The integrated Traditional Chinese and Western medicine nursing showed positive effect on treatment outcome, patient quality of life and prognosis of disease, and the effect of integrative nursing intervention was superior to routine nursing. (目的 观察中西医结合护理干预高危糖尿病足患者的效果, 及对患者生活质量及预后的影响, 为高危糖尿病足患者采取更好的护理策略、制定更为合理的护理干预方案提供依据。方法 从医院2021年1月—2022年1月收治的200例2型糖尿病患者中筛查出40例高危糖尿病足患者, 随机分为现察组与对照组, 各20例。对照组采取常规护理干预, 观察组在常规护理基础上, 给予中西医结合护理干预。评价两组干预效果, 以及对患者生活质量以及足部状况影响。结果 观察组干预效果优于对照组, 差异有统计学意义(P＜0. 05); 观察组生活质量评定问卷(GQOL-74)评分改善率85. 00%(17/20), 高于对照组的65. 00%(13/20), 但差异无统计学意义(P＞0. 05); 观察组足部感染和足部溃疡发生率低于对照组, 差异有统计学意义(P＜0. 05), 观察组无1例患者截肢, 对照组3例患者截肢。结论 中西医结合护理干预能进一步提高高危糖尿病足患者的治疗效果, 改善患者生活质量及预后, 干预效果要优于常规护理干预。)